2016
DOI: 10.1097/qad.0000000000001064
|View full text |Cite
|
Sign up to set email alerts
|

Bryostatin-1 for latent virus reactivation in HIV-infected patients on antiretroviral therapy

Abstract: Bryostatin-1 was safe at the single doses administered. However, the drug did not show any effect on PKC activity or on the transcription of latent HIV, probably due to low plasma concentrations. This study will inform next trials aimed at assessing higher doses, multiple dosing schedules or combination studies with synergistic drugs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
161
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 178 publications
(161 citation statements)
references
References 33 publications
0
161
0
Order By: Relevance
“…These include the HDACis vorinostat (Archin et al, 2017; Archin et al, 2012; Elliott et al, 2014), panobinostat (Rasmussen et al, 2014) and romidepsin (Sogaard et al, 2015), the disulfiram drug shown to affect PI3K/Akt and more commonly used to treat alcoholism (Elliott et al, 2015; Spivak et al, 2014; Xing et al, 2011), and the TLR9 agonist MGN1703 (Vibholm et al, 2017). The PKC agonist bryostatin was also evaluated in vivo but had no effect on the transcription of latent HIV (Gutierrez et al, 2016). In these clinical studies, all LRAs except bryostatin increased HIV RNA transcription when administered alone, but there was no decline in the number of infected cells (Archin et al, 2012; Elliott et al, 2015; Elliott et al, 2014; Gutierrez et al, 2016; Rasmussen et al, 2014; Sogaard et al, 2015).…”
Section: Latency Reversing Agentsmentioning
confidence: 99%
See 2 more Smart Citations
“…These include the HDACis vorinostat (Archin et al, 2017; Archin et al, 2012; Elliott et al, 2014), panobinostat (Rasmussen et al, 2014) and romidepsin (Sogaard et al, 2015), the disulfiram drug shown to affect PI3K/Akt and more commonly used to treat alcoholism (Elliott et al, 2015; Spivak et al, 2014; Xing et al, 2011), and the TLR9 agonist MGN1703 (Vibholm et al, 2017). The PKC agonist bryostatin was also evaluated in vivo but had no effect on the transcription of latent HIV (Gutierrez et al, 2016). In these clinical studies, all LRAs except bryostatin increased HIV RNA transcription when administered alone, but there was no decline in the number of infected cells (Archin et al, 2012; Elliott et al, 2015; Elliott et al, 2014; Gutierrez et al, 2016; Rasmussen et al, 2014; Sogaard et al, 2015).…”
Section: Latency Reversing Agentsmentioning
confidence: 99%
“…The PKC agonist bryostatin was also evaluated in vivo but had no effect on the transcription of latent HIV (Gutierrez et al, 2016). In these clinical studies, all LRAs except bryostatin increased HIV RNA transcription when administered alone, but there was no decline in the number of infected cells (Archin et al, 2012; Elliott et al, 2015; Elliott et al, 2014; Gutierrez et al, 2016; Rasmussen et al, 2014; Sogaard et al, 2015). In one clinical trial, the combination of the HDACi romidepsin with a T-cell vaccine led to a modest reduction in HIV DNA, although the mechanism for this reduction was not explored (Leth et al, 2016).…”
Section: Latency Reversing Agentsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, direct quantitation of cell-associated viral protein following clinical administration of HDACis has not been possible. Other agents, such as bromodomain inhibitors and protein kinase C (PKC) agonists, have also been shown to induce viral transcription in vitro and in preclinical models and are under further evaluation as potential clinical HIV "shock" agents (6,(12)(13)(14)(15)(16). Worth noting, the induction of viral protein expression is a prerequisite for several investigational immune-mediated "kill" strategies (3)(4)(5).…”
Section: Introductionmentioning
confidence: 99%
“…Protein kinase activators like Bryostatin, Ingenols and Prostratin were among the initial members to demonstrate in vitro activation of engineered cell lines bearing HIV proviruses. Their unacceptable cytotoxicity limitations [8,9] prevented their trials in vivo or resulted in failure of HIV rebound in performed trial [10]. However modified bryostatin analogs with lowered toxicity have recently shown promising viral rebound in engineered humanized BLT mice [11].…”
Section: Editorialmentioning
confidence: 99%